Recollections of the Last Four Popes and of Rome in Their Times - Wiseman, H. E. (Hurst and blackett, Publishers, 1858)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage; 6.Yellowing 變黃